Biotechnique of rearing Beluga (H.huso) using brackishwater of the Caspian Sea (Different densities and water flow) - Pourali Foshtomi, Hamidreza; Bahmani, M.; Jamalzad, F.; Mohseni, M.; Ashori, A.R.; Hossinnia, E.; Arshad, A.; Sadeghi, M. (Iranian Fisheries Science Research Institute, 2011)
This study was conducted at the Applied Research Station for Sturgeon Culture (Chaboksar site) and was supported by the Iranian Fisheries Research Organization in order to obtain the bio technique for Huso huso culture in brackish water from the Caspian Sea. The effects of stocking density and water flow at the inlet of brackish water was studied for a period of 4 years using 4 weight classes and the results obtained were compared with those obtained from the culture of H. huso in freshwater. Huso huso in four weight classes of 3-20 g, 20-200 g, 325-1000 g and 1000-3000 g were stocked at stocking densities between 350 g to 15 kg m-2. The effect of water flow in rearing tanks was studied in weight classes 30- 2700 g. In the weight class 3-20 g, highest growth was recorded in H. huso stocked at 1000 g m-2 in brackish water which was significantly higher (P<0.5) than that recorded in freshwater suggesting the advantage of rearing H. huso in brackish water at improved density of 1000 g m-2. Results obtained from total length in juvenile H. husoconform to these results. It may therefore be concluded that in the weight class 3-20 g, stocking density of 1000 g m-2 is not a limiting factor on growth in juvenile H. huso. Low specific growth rate (SGR) was reported with a stocking density of 1500 g m-2 in freshwater which was not significantly different from that in brackish water. Hence rearing juvenile H. huso in brackish water at high densities (1500 g m-2) is preferred to rearing in freshwater as H. huso is more capable of adapting to stressful conditions of stocking density in brackish water. Similar trends were observed for percentage body weight increase (BWI%) showing the advantage of using a stocking density of 1000 g m-2 in brackish water. Production in different groups showed variations depending on stocking density biomass. Condition factor was low when H. huso was reared in freshwater at a stocking density of 1500 g m-2. Similarly CVw was low in the experimental group reared at a density of 500 g m-2 in ...